Exploring the Understanding Shift of Maskumambang Boarding School: From Scripturalist Aswaja Salafiyah to Modern Contextualist Salafiyah - Hadi, Abd; Mu’ammar, Muhammad Arfan (Journal of Pedagogy and Education Science, 2023)
This descriptive qualitative analysis explores the understanding shift of Maskumambang Gresik Islamic Boarding School from the Aswaja scripturalist mindset to the scripturalist Salafiyah Wahabiyah mindset and then to the modernist and contextualist Salafiyah mindset. The study aims to understand the reasons behind the shift and the implications on the religious practices of the students and alums. The findings reveal that the religious ideology of the boarding school shifted over time under different leaders, which also influenced the spiritual implications of the students and alums. During the traditionalist Salafiyah era, the spiritual practices were in line with the Aswaja model, while under the Wahabiyah Salafiyah era, patterns shifted to eliminate nuances of T.B.C. (tahayul, bid’ah, churafat). Under the modernist and contextual Salafiyah era, practices evolved to focus on societal benefit and justice. The study highlights the importance of understanding the shifts in religious understanding and its impact on the rules and beliefs of the students and alums of Islamic boarding schools.